Recent Advances in Computed Tomographic Technology: Cardiopulmonary Imaging Applications. Issue 2 (March 2017) - Tabari, Azadeh; Lo Gullo, Roberto; Murugan, Venkatesh; Otrakji, Alexi; Digumarthy, Subba; Kalra, Mannudeep
Abstract : Cardiothoracic diseases result in substantial morbidity and mortality. Chest computed tomography (CT) has been an imaging modality of choice for assessing a host of chest diseases, and technologic advances have enabled the emergence of coronary CT angiography as a robust noninvasive test for cardiac imaging. Technologic developments in CT have also enabled the application of dual-energy CT scanning for assessing pulmonary vascular and neoplastic processes. Concerns over increasing radiation dose from CT scanning are being addressed with introduction of more dose-efficient wide-area detector arrays and iterative reconstruction techniques. This review article discusses the technologic innovations in CT and their effect on cardiothoracic applications.